1992
DOI: 10.1182/blood.v79.1.138.bloodjournal791138
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecules on freshly recovered T leukemias promote tumor- directed lympholysis

Abstract: Besides facilitating cell to cell adhesion, the molecular interactions between CD2 and its ligand CD58 (lymphocyte function-associated antigen- 3 [LFA-3]), as well as between CD11a/18 (LFA-1) and CD54 (intercellular adhesion molecule-1) have recently been recognized to participate in lymphocyte activation, recirculation, and effector function, including cytolytic activity towards tumor cells. We have investigated the role of CD2/CD58 and CD11a/18/CD54 interactions in cellular immune responses directed towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…CD58 is an important adhesion molecule expressed at distinct levels in a variety of normal cells and tumor cells [ 49 ]. The costimulatory signaling of CD58 facilitates CTL activation, proliferation, and cytotoxicity [ 14 ], while CD58 loss may contribute to a reduction in the recognition and adhesion of T/NK cells to tumor cells in tumor microenvironment [ 20 ]. Genomic inactivation of CD58 resulted in the loss of expression, which was an adverse prognostic factor for diffuse large B-cell lymphoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD58 is an important adhesion molecule expressed at distinct levels in a variety of normal cells and tumor cells [ 49 ]. The costimulatory signaling of CD58 facilitates CTL activation, proliferation, and cytotoxicity [ 14 ], while CD58 loss may contribute to a reduction in the recognition and adhesion of T/NK cells to tumor cells in tumor microenvironment [ 20 ]. Genomic inactivation of CD58 resulted in the loss of expression, which was an adverse prognostic factor for diffuse large B-cell lymphoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to promoting adhesion between cells, the molecular interaction between CD2 and its ligand CD58 has been thought to be involved in lymphocyte activation and effector functions, including cytolytic activity on neoplastic cells [ 14 16 ]. Intriguingly, under normal physiological conditions, as non-malignant B cells differentiate from early to mature stages in the bone marrow, CD58 expression was profoundly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Once leukaemic blasts have entered the blood, expression of CD54 could also render them susceptible to NK-or LAK cell-mediated lysis, and therefore diminish their number. In vitro data suggest a role for CD54 and CD58 in mediating cytolytic activity towards tumour cells (Schirren et al, 1992;Archimbaud et al, 1994). Leukaemic blasts might acquire a selective advantage by down-regulating or shedding these receptors, and therefore escape from host tumour surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies focusing on expression patterns of adhesion receptors in haematological malignancies have been published (Maio et al, 1990;Horst et al, 1991;Nambu et al, 1992;Dolcetti et al, 1992;Reuss-Borst et al, 1992Pinto et al, 1993). It has been hypothesized that CD54 expression by leukaemic blasts could increase their susceptibility to lysis by non-HLA-restricted cytotoxic cells such as natural killer (NK) and lymphokine activated killer (LAK) cells (Gregory et al, 1988;Schirren et al, 1992;Archimbaud et al, 1994). Hence, down-regulation of CD54 could enable tumour cells to escape from host immunosurveillance.…”
mentioning
confidence: 99%
“…For example, incubation of B lymphoblastoid cell with immobilized anti-CD58 mAbs causes broad tyrosine phosphorylation and increases TNF-α production ( 15 ). Accumulating evidence has demonstrated that the CD2-CD58 interaction plays a critical role in lymphocyte activation, recirculation, and effector function, e.g., cytolytic activity on neoplastic cells ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%